2009
DOI: 10.5194/nhess-9-1075-2009
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of human immediate response capability related to tsunami threats in Indonesia at a sub-national scale

Abstract: Abstract. Human immediate response is contextualized into different time compartments reflecting the tsunami early warning chain. Based on the different time compartments the available response time and evacuation time is quantified. The latter incorporates accessibility of safe areas determined by a hazard assessment, as well as environmental and demographic impacts on evacuation speed properties assessed using a Cost Distance Weighting GIS approach.Approximately 4.35 million Indonesians live in tsunami endan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
70
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 17 publications
0
70
0
2
Order By: Relevance
“…Post et al (2009b) concluded that a quantification of the reaction time, i.e. the time that passes between receiving a warning by people at risk, to their decision to start evacuating, is currently not possible due to insufficient availability of required data.…”
Section: Parametermentioning
confidence: 99%
See 2 more Smart Citations
“…Post et al (2009b) concluded that a quantification of the reaction time, i.e. the time that passes between receiving a warning by people at risk, to their decision to start evacuating, is currently not possible due to insufficient availability of required data.…”
Section: Parametermentioning
confidence: 99%
“…Following Post et al (2009b), the time spans related to (1), i.e. warning decision time (time consumed by detection of a potentially tsunamigenic earthquake until the decision to disseminate a warning) and warning dissemination time (time consumed by technical transmission of the warning from the warning center to local devices and institutions and further transmission from there to the people at risk), are presumed as five and three minutes respectively.…”
Section: Parametermentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the modeling part -and focusing on coastal inundation -exemplary reference can be made to the work of Borrero et al (2006), who used the MOST model (Titov and González, 1997) for tsunami generation and inundation in western Sumatra; Gayer et al (2010), who used the MIKE21 Flow Model FM to simulate inundation based on roughness maps for Indonesia; Omira et al (2010), who applied a modified version of the COMCOT model (Liu et al, 1998) to selected cases in Casablanca, Morocco; Apotsos et al (2011), who used the Delft3D model to study inundation and sediment transport by the 2004 SE Asia tsunami in measured and idealized morphologies; and Løvholt et al (2012), who used models based on the Boussinesq equations for tsunami propagation and nonlinear shallow-water wave equations for coastal inundation to simulate the 2011 Tohoku tsunami. Extending to coastal planning, vulnerability assessment and tsunami hazard mitigation, one may refer to the work of Bernard (2005), González et al (2009), Post et al (2009, Kumar et al (2010), Sørensen et al (2012) and González-Riancho et al (2014).…”
Section: Introductionmentioning
confidence: 99%
“…To support tsunami preparedness and education efforts, there has been considerable work in recent years to characterize population vulnerability to tsunamis, including exposure assessments (Wood 2007;Lovholt et al 2012), demographic sensitivity analyses (Wood et al 2010), pedestrian evacuation modeling (e.g., Jonkmann et al 2008;Post et al 2009;Yeh et al 2009;Schmidtlein 2012, 2013;Freire et al 2013), and vertical evacuation siting (Park et al 2012;Wood et al 2014). All of these efforts contribute to understanding whether or not at-risk populations would have sufficient time to evacuate hazard zones before tsunami waves arrive and for recognizing what landscape or demographic characteristics may hinder their ability to evacuate.…”
mentioning
confidence: 99%